Analisis Total Oxidation Value Minyak Goreng Bekas pada Beberapa Produk Olahan Pangan di Pasaran - Pratiwi, Nindya Putri Cossy; Meikapasa, Ni Wayan Putu (Jurnal Teknologi dan Mutu Pangan, 2025)
Repeated use of cooking oil at high temperatures encourages this oxidation of oil. This condition often creates a dilemma, on the one hand for traders tend to prioritize economic value over health aspects. This research aims to identify and analyze the TOTOX value in used cooking oil which is used by food sellers in the Merak neighborhood, Banten. Research methods is a laboratory experiment by taking 5 samples of used cooking oil Random from different sellers. The research results show that the lowest peroxide value was found in catfish pecel sellers (0.57 mek O2/kg) and highest among gado-gado sellers (2.84 mek O2/kg), but still below the maximum limit. P-anisidine value with the highest levels among warteg sellers (22.57) and the lowest among sellers of flour fried chicken (0.98). Mark TOTOX with the highest levels at warteg sellers (27.57 mek O2/kg) and the lowest at seller of flour fried chicken (5.30 mek O2/kg). All used cooking oils are tested in This researchstill meets the requirements for peroxide figures. However, there are three sellers (Warteg, Pecel Lele, and Gado-gado) which has a TOTOX value exceeding the permitted limit. Therefore, it is important to carry out routine monitoring of The quality of used cooking oil, especially from sellers who have a high TOTOX value, is useful ensure consumer safety.